Biology and life cycle of Amblyomma incisum (Acari: Ixodidae) - Szabo, Matias Pablo J.; Pereira, Lucas de F.; Castro, Marcio B.; Garcia, Marcos V. [UNESP]; Sanches, Gustavo S. [UNESP]; Labruna, Marcelo B. (Springer, 2009)
Amblyomma incisum Neumann is a major tick species in the Atlantic Forest of Brazil. Tapir is the main host for adult ticks and a high aggressiveness of nymphs to humans has been reported. In this work data on the biology and life cycle of this tick species is presented for the first time. It was shown that horse is a suitable host for A. incisum adults and rabbit for larvae and nymphs. It was also shown that A. incisum is a big tick species (mean engorged female weight of 1.96 g) with a long life cycle which lasts 262.3 days when maintained at 27A degrees C and 85% RH. These laboratory conditions were, however, inappropriate and egg hatching rate (1.2%) was very low. Nevertheless egg hatching of ticks in a forest patch increased considerably (72.2%) indicating that this A. incisum population is highly dependent on a forest-like environment.
Keywords: Amblyomma incisum; Horse; Rabbit; Ixodidae; Life cycle; Atlantic rain forest